2018
DOI: 10.3102/0013189x18800047
|View full text |Cite
|
Sign up to set email alerts
|

California DREAM: The Impact of Financial Aid for Undocumented Community College Students

Abstract: Ineligibility for state financial aid has traditionally limited undocumented students’ access to higher education. Since 2013, the California Development, Relief, and Education for Alien Minors Act (CA-DREAM) has made state-supported aid available to undocumented college students with demonstrated financial need. We use a difference-in-difference strategy and administrative data to examine the impact of the policy on undocumented community college students’ enrollment behaviors and postsecondary outcomes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 32 publications
0
31
0
5
Order By: Relevance
“…These constraints and systemic barriers may explain why undocumented students on average are hyper‐selected into community colleges, that is, entering college more academically prepared (e.g., higher incoming GPAs) than their peers with legal status (Hsin & Reed, 2020; Ngo & Astudillo, 2019). Accordingly, undocumented students in community colleges tend to outperform their peers with legal status, having higher likelihoods of completing a degree (Conger & Chellman, 2013; Hsin & Reed, 2020).…”
Section: Undocumented Community College Studentsmentioning
confidence: 99%
See 2 more Smart Citations
“…These constraints and systemic barriers may explain why undocumented students on average are hyper‐selected into community colleges, that is, entering college more academically prepared (e.g., higher incoming GPAs) than their peers with legal status (Hsin & Reed, 2020; Ngo & Astudillo, 2019). Accordingly, undocumented students in community colleges tend to outperform their peers with legal status, having higher likelihoods of completing a degree (Conger & Chellman, 2013; Hsin & Reed, 2020).…”
Section: Undocumented Community College Studentsmentioning
confidence: 99%
“…Researchers who have examined the impact of policies providing financial aid in addition to the in‐state tuition discount have found significant positive effects on college enrollment and persistence (Bozick et al., 2016; Holzman, 2016; Ngo & Astudillo, 2019). For example, California, the state with the largest population of undocumented immigrants, implemented the California DREAM Act (CA DREAM) in 2013, providing access to state grant aid for low‐income undocumented students (Assembly Bill 131, 2011).…”
Section: Supportive Policymentioning
confidence: 99%
See 1 more Smart Citation
“…Research shows positive effects of offering in‐state tuition and state financial aid to undocumented students, as it increases college enrollment and improves outcomes such as academic achievement, credits attempted, and first‐semester retention (Flores 2010a, 2010b; Flores and Horn 2009; Kaushal 2008; Ngo and Astudillo 2019). However, research to date has found no evidence that these policies improve completion rates (Darolia and Potochnick 2015).…”
Section: Main Barriers To Postsecondary Affordability Access and Sumentioning
confidence: 99%
“…The California DREAM act has yielded positive results for the undocumented Hispanic student population when compared with U.S. citizens. Ngo and Astudillo (2019) found that undocumented Hispanic students “completed more units in their first quarter of enrollment, had higher attempt-to-completion rations, and were more likely to enroll in a second quarter” (p. 10).…”
Section: Power Of States—undocumented Students Pursuing Higher Educationmentioning
confidence: 99%